Understanding Suicide, Drug and Alcohol Deaths in Northern Ireland: Socio-economic and Household Insights (2011-2022) - Hughes, John; Foley, Brian; Colohan, Carmel; Lyness, Deborah (International Journal of Population Data Science, 2025)
Objectives Suicide, drug-related and alcohol-specific deaths have increased in Northern Ireland over the last decade, disproportionately affecting young men. Official statistics rely on death certificates. This study links Census and mortality data to examine how individual, household and area factors are associated with these deaths. Methods The 2011 Census was linked to deaths registered until September 2022 (Northern Ireland Mortality Study) to analyse how personal, household and area factors influenced mortality. The study included 1.11 million records (ages 16-64) with 1,649 suicides, 1,049 drug-related and 3,675 alcohol-specific deaths. Descriptive analyses compared deceased individuals’ baseline characteristics with the general population. Cox regression models identified the most at-risk groups for each death type, with separate analyses for males and females due to differing characteristics. Results Suicide, drug and alcohol deaths were more common among males, the economically inactive, those without qualifications, individuals with mental illnesses or disabilities, social renters, and residents of Greater Belfast or deprived areas. Modelling findings showed that lack of formal qualifications increased suicide and drug-related mortality risk in males. Unemployment was a major risk factor for males, while economic inactivity increased risk for females. Mental illness was strongly associated with suicide and drug-related deaths, while disability increased drug-related and alcohol-specific mortality risk. Among males, living alone increased risk across all causes. Among females, being single or separated/divorced increased mortality risk for drug and alcohol deaths. Male children in lone-parent households had higher suicide and alcohol mortality risk, while female lone parents had elevated drug-related mortality risk. Conclusion Suicide, drug-related, and alcohol-specific deaths disproportionately affect males, socio-economically disadvantaged individuals, and those with mental illness. Risk factors vary by sex and living situation. Targeted policies addressing mental health, substance use and socio-economic inequalities remain crucial in reducing mortality risks.